Cisternal myelography using Conray - Hitchcock, Edward (1973)
Conray-280 (meglumine iothalamate) can be injected safely into the cisterna magna in the human. In this series of 46 patients no complications were encountered attributable to the irritant effects of Conray. Satisfactory radiographic visualization was obtained in 87% of cases using 5 ml. 50% solution of Conray-280 enabling clear delineation of the anterior and posterior borders of the spinal cord to be made.